Electric Field Effect in Two‐Dimensional Transition Metal Dichalcogenides. (20th December 2016) - Liu, Fucai; Zhou, Jiadong; Zhu, Chao; Liu, Zheng
Abstract : Two‐dimensional (2D) materials have been an emerging platform for future device applications. Among them, 2D transition metal dichalcogenides (TMDs) have attracted substantial interest because of their fascinating properties ranging from semiconductor, semimetal, metal, to superconductor. The electric controllability over their physical properties is extremely important for their device application. This feature article presents recent progress in the electrical manipulation of the optical, electric, and spin/valley dependent properties of 2D TMDs. Also, some of the outstanding challenges and opportunities in this promising research field are highlighted. Abstract : The outstanding electric, optical, and valleytronic properties of 2D transition metal dichalcogenides (TDMDs) make them promising for device applications, while the electric controllability is extremely important for demonstrating their device application. In this review, we highlight the recent progress on the electric controllability of 2D TMDs and provide the opportunities that need to be investigated.